KARUMGA: Perancangan dan Penerapan Sistem Informasi Penggunaan Aset KARUMGA (Kasi Rumah Tangga) Berbasis Website di Pondok Pesantren Nurul Jadid - Bahar, Hasbul (Universitas Nurul Jadid, 2020)
Nurul Jadid Islamic Boarding School is an Islamic educational institution without having an asset management system. Located in East Java Province with huge numbers of assets, this instituion has been managed without information system of asset control in schools, either formal or non-formal. This study is to design and implement a web based information system namely KARUMGA (Kasi Rumah Tangga) in inputting, editing, and searching the required asset data, making reports of Nurul Jadid’s assets more effective and efficient. The design of an efficient Web Based Asset Management application system is inteded to provide a fast and responsive service to lending pesantren assets.